2018
DOI: 10.1021/acs.cgd.7b01808
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Structures, Stoichiometric Diversity, and Bench Stability of Cocrystals with a Volatile Halogen Bond Donor

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…A detailed description of the experimental setup and its use in monitoring cocrystal formation have been recently published. 30,42…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the experimental setup and its use in monitoring cocrystal formation have been recently published. 30,42…”
Section: Resultsmentioning
confidence: 99%
“…Where large quantities of halogen-bonded materials are desired (>100 mg), crystallization methods requiring solvent evaporation or solvent diffusion can be tedious to perform, often requiring many days or perhaps weeks to achieve the desired product in sufficient quantity. Mechanochemistry has been shown to be a favorable route for the halogen bond synthon, 54,59,60,61,62 offering a scalable and rapid method of preparing halogen-bonded cocrystals, 63,64 all without the need of large volumes of solvents. However, mechanochemistry by ball milling 65 has the inconvenience of yielding powdered products, requiring further manipulations in order to prepare a sample for SCXRD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The cocrystal ( tftib )( PPh 3 ) was obtained as a part of our program in exploring XB to unusual acceptors 21 . Slow evaporation of an equimolar solution of tftib and PPh 3 in acetonitrile gave colorless crystals that were characterized by single crystal X-ray diffraction at 103 K. Structure determination revealed that asymmetric unit consists of one molecule each of tftib and PPh 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%